Desalination performance in versatile capacitive/battery deionization configurations using a cation intercalating electrode - Tarus, Bethwel Kipchirchir; Ullah, Zahid; Jande, Yusufu A. C.; Njau, Karoli N.; Byun, Jeehye; Son, Moon (Elsevier BV, 2024)
Capacitive deionization (CDI) is an alternative desalination technique for low -to -moderate salinity feeds. Despite significant advances in electrode material design, CDI ' s thermodynamic energy efficiency ( TEE ) remains low and has become important in assessing feasibility for real -world applications. Innovative cell configurations are key to improving TEE ; however, their performance trends need to be contextualized, given the scattered information that can be challenging to compare. This study evaluates various desalination cells, including conventional CDI, single- and multi -channel asymmetric CDI, and multi -channel battery deionization (BDI). Using MoS 2 as a representative intercalating material, the position of active sites on composite electrodes was first optimized. Hydrothermally-grown MoS 2 on carbon nanofibers exhibited enhanced charge transfer compared to MoS 2 embedded in nanofibers. Among the tested configurations using 20 mM NaCl in single -pass mode and 50% water recovery, BDI demonstrated over 3.7 times higher TEE than asymmetric setups and 50 times higher than typical CDI while maintaining consistent desalination performance. BDI benefited from the combined effects of electrosorption/intercalation and ion exchange membranes in symmetric conformation, effectively utilizing charge. These findings provide insights into process engineering for improved electrochemical desalination and the enhancement of ion intercalation -based desalination configurations.